Saudi Arabian 2030 Vision and Entrepreneurial Intention Among University Students (2021)
The purposes of this study are to report the degree of the Kingdom of Saudi Arabian 2030 Vision’s (KSA 2030 Vision) awareness among students, and to examine the association of entrepreneurial intention with the awareness of the KSA 2030 Vision in College